Outcomes of balloon angioplasty and stent placement for iliac artery lesions classified as TASC II A, B: a single-center study - Duc Tin, Le; Van Nut, Lam; Abdalla, Abdelrahman Sherif; Duc, Hoang; Kwaah, Patrick A.; Le, Trang T. B.; Vy, Tran Thi Thuy; Le, Thoa; Anh, Pham Minh; Kim Que, Do; Huy, Nguyen Tien (Frontiers in Surgery, 2024)
Background: Iliac artery stenosis or occlusion is a critical condition that can severely impact a patient's quality of life. The effectiveness of balloon angioplasty and intraluminal stenting for the treatment of iliac artery lesions classified as TASC II A and B was evaluated in this single-center prospective study. Methods: Conducted between October 2016 and September 2020 at Cho Ray Hospital's Vascular Surgery Department, this prospective study involved PAD patients categorized by TASC II A and B classifications who underwent endovascular intervention. Intervention outcomes were assessed peri-procedure and during short-term and mid-term follow-ups. Results: Of the total of 133 patients, 34.6% underwent balloon angioplasty, while 65.4% received stenting. The immediate technical success rate was 97.7%, while the clinical success rate was 62.4%. Complications were minimal, with major limb amputation reported in 1.5% of the cases. There was a significant improvement in Rutherford classification and ABI at short-term follow-up, with a patency rate of 90.2%. The mid-term post-intervention follow-up yielded similar results with an 86.1% patency rate. The overall mortality rate was 20.3% during the follow-up period. Conclusion: Balloon angioplasty and stent placement are effective and safe interventions for TASC II A and B iliac artery occlusions with favorable short and mid-term outcomes. Further, multi-center studies with larger sample sizes are recommended for more comprehensive conclusions, including long-term follow-up assessment.